Ecologising Invited and Uninvited Patient Participation in Russia - Vlas Nikulkin; Yan Vlasov; Olga Zvonareva (Wiley, 2024)
ABSTRACT Introduction Public participation can be both supported and limited by decision‐makers. Therefore, citizens either participate in top‐down approved formats or have to turn towards subversion. These different participation practices, called invited and uninvited, are often treated by researchers as mutually exclusive. In this article, we present the case of patient organisations' involvement in various state‐controlled deliberation bodies in Russia, which does not fit into a smooth binary distinction of the patient participation practice. Instead, identified patient participation practices combine interaction approved by gatekeepers with interaction, which are subversive and grassroots‐initiated. Conceptually, it means that invited and uninvited participation can be better understood as intertwined ecologies. Methods The article is based on a qualitative ethnographic study, which includes participatory observations of the meetings of state‐controlled public participation bodies, such as public councils, 51 semi‐structured interviews with members of these bodies and an analysis of the relevant policy and methodological documents. Informed consent to record and transcribe all interviews was obtained. Thematic analysis has been used to produce the results. Results Russian patient organisations often work informally and independently of state‐approved practices expected from them. Some subversive practices happen outside official meetings, others become widely used best practices and others remain everyday mundane interactions, which contribute to the maintenance of the independence of patient organisations against otherwise dominating and nondemocratic state actors. Conclusion The ecologising approach to patient participation, which interprets invited and uninvited practices as interconnected, has better explanatory power for cases in which citizens maintain independence despite all limitations associated with authoritarian settings. Conceptualising invited and uninvited practices as situations, or separate time‐ and space‐bound events, is a helpful theoretical framework for understanding diverse and seemingly contradictory public participation practices. Patient or Public Contribution Research participants communicated amendments to the initial research framework to incorporate their needs. Repeated interviews allowed triangulation of preliminary findings with research participants. The article is co‐authored with the patient organisation representative, who has contributed directly to data analysis and presentation.